Preparation, characterisation and evaluation of curcumin with piperine-loaded cubosome nanoparticles. (September 2014) - Tu, Y. S.; Fu, J. W.; Sun, D. M.; Zhang, J. J.; Yao, N.; Huang, D. E.; Shi, Z. Q.
Abstract Objective: In this study, curcumin was designed into the nanoformulation called cubosome with piperine in order to improve oral bioavailability and tissue distribution of curcumin. Methods: The characteristic of the cubosome was studied by using scanning electron microscope (SEM), Infrared spectrum and small angle X-ray scattering (SAXS) techniques. Tissue distribution of cubosome was measured by liquid chromatography-mass spectrometry (LC-MS) method in mice. Results: The characteristic of the cubosome was demonstrated that the curcumin and piperine were encapsulated in the interior of the cubosome and the crystal form was Pn3m space. The pharmacokinetic test revealed that the cubosome could improve the oral bioavailability significantly compared to the suspension of curcumin with piperine and be mainly absorbed by the spleen. Conclusion: These findings provide the reference to a preferable choice of the curcumin formulation and contribute to therapeutic application in clinical research.